Pathogenical meaning of serotoninergic mechanisms in the development of idiopatic generalised forms of epilepsy - N. B. Gubanova; Yu. V. Karakulova (Бюллетень сибирской медицины)
Neurotransmitters disturbances with the certain role of serotoninergic system are in the basis of pathogenesis of epilepsy. 46 patients (29 females, 17-males) with idiopatic generalized epilepsy (mean age 21,8 ± 1,82) were investigated. In 30,4% of patients depressive disorders were revealed. Significant decreasing of blood serotonin level in patients with during the interictal period which decreased more after the generalised convulsive and myoclonic seasures was found by the immune assay method.